Border crossings to neighboring countries: Analysis of the opportunities and challenges of catenary trucks for freight transport to neighboring regions of Baden-Wuerttemberg - Martin Wietschel; Uta Burghard; Patrick Plötz (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
Significant shares of the heavy-duty freight transport found on the roads in Baden-Wuerttemberg are transborder transportations. This working paper therefore focuses on a discussion of border crossings to neighboring countries (especially France, Switzerland, and Austria) in relation to catenary trucks and other alternative powertrains in heavy-duty road freight transport. This involved a one-day workshop with experts representing energy supply, freight transport and transport infrastructure from Baden-Wuerttemberg and its neighboring countries, which took place at the beginning of 2020. The workshop's objectives were to discuss practical experiences and pass them on to countries that have not yet taken action. – – Nennenswerte Teile des schweren Güterverkehrs auf baden-württembergischen Straßen sind grenzüberschreitend. Gegenstand dieses Workingpapers ist daher eine Diskussion der Schnittstellen zum angrenzenden Ausland (insbesondere Frankreich, Schweiz, Österreich) in Bezug auf Oberleitungs-Lkw und weitere alternative Antriebe im schweren Straßengüterverkehr. Dies umfasst einen eintägigen Workshop mit Experten der Energieversorgung, des Güterverkehrs und der Verkehrsinfrastruktur aus Baden-Württemberg und den angrenzenden Staaten, welcher Anfang 2020 stattgefunden hat. Die Ziele des Workshops waren es, praktische Erfahrungen zu diskutieren und an bisher noch nicht aktive Länder weiterzugeben.
urn:nbn:de:0011-n-5864024
Keywords: 330; Straßengüterverkehr; Internationaler Güterverkehr; Experten; Energieversorgung; Verkehrsinfrastruktur; Baden-Württemberg